1982
DOI: 10.1159/000123288
|View full text |Cite
|
Sign up to set email alerts
|

GABA Neuron Systems in Hypothalamus and the Pituitary Gland

Abstract: The distribution of γ-aminobutyric acid (GABA) nerve fibers and cell bodies in the rat hypothalamus and pituitary gland was immunohistochemically examined using antibodies against the GABA-synthesizing enzyme glutamate decarboxylase (GAD). A dense network of GAD-positive nerve fibers was observed to be essentially evenly distributed throughout the hypothalamus. A plexus of GABA terminals was also demonstrated both in the median eminence and within the posterior and intermediate lobes of the pituitary. Three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(61 citation statements)
references
References 17 publications
(35 reference statements)
2
58
0
1
Order By: Relevance
“…GAD and GABA immunoreactive fibers are found throughout the hypothalamus, as suggested in the present study using antiserum against GAD and GABA, and in previous biochemical or immunocytochemical studies with GAD antiserum (Tappaz et al, 1982(Tappaz et al, , 1983Vincent et al, 1982). In all areas containing TH immunoreactive neurons, GAD and GABA immunoreactive axons are numerous.…”
Section: Gaba Innervation Of Hypothalamic Dopaminergic Neuronssupporting
confidence: 87%
“…GAD and GABA immunoreactive fibers are found throughout the hypothalamus, as suggested in the present study using antiserum against GAD and GABA, and in previous biochemical or immunocytochemical studies with GAD antiserum (Tappaz et al, 1982(Tappaz et al, , 1983Vincent et al, 1982). In all areas containing TH immunoreactive neurons, GAD and GABA immunoreactive axons are numerous.…”
Section: Gaba Innervation Of Hypothalamic Dopaminergic Neuronssupporting
confidence: 87%
“…Hypothalamic nuclei reported to contain the highest densities of GAD-immunoreactive fibers and neuropil include the following: arcuate nucleus, dorsomedial nucleus, ventral medial nucleus, perifomical region, medial and lateral parts of the mamillary body, median eminence, suprachiasmatic nucleus, and preoptic area; other related nuclei containing high densities include the fields of Fore1 and bed nucleus of the stria terminalis. After colchicine injections, GAD-immunoreactive cells became visible in the arcuate nucleus, perifomical region, and regions lateral and posterior to the medial mamillary nucleus (Vincent et al, 1982b).…”
Section: Hypothalamusmentioning
confidence: 99%
“…All have remarked on the very high density of immunoreactive fiber and neuropil staining and the difficulty of identifying immunoreactive cell somata without colchicine treatment (e.g., Perez de la Mora et al, 198 1;Vincent et al, 1982b, Tappaz et al, 1983Mugnaini and Oertel, 1985;Van den Pol, 1986). Hypothalamic nuclei reported to contain the highest densities of GAD-immunoreactive fibers and neuropil include the following: arcuate nucleus, dorsomedial nucleus, ventral medial nucleus, perifomical region, medial and lateral parts of the mamillary body, median eminence, suprachiasmatic nucleus, and preoptic area; other related nuclei containing high densities include the fields of Fore1 and bed nucleus of the stria terminalis.…”
Section: Hypothalamusmentioning
confidence: 99%
“…However, recent studies indicated that suramin does not block exclusively P 2 purinoceptors; it also inhibits glutamate and GABA receptor-mediated currents (Nakazawa et al 1995), as well as the coupling of receptors to G proteins (Beindl et al 1996). Since the posterior lobe receives a well-defined GABAergic innervation from central nuclei (Oertel et al 1982, Vincent et al 1982, Buijs et al 1987 and AVP release in the pituitary is modulated by GABA-A receptors (Anderson & Mitchell 1986, Sladek & Armstrong 1987, Magnuson & Meyerson 1993, augmentation of oxytocin and AVP release by suramin could be explained by the removal of GABAergic regulatory influence. Glutamate immunoreactivity (Meeker et al 1991) and metabotropic glutamate receptor subtypes (Kiyama et al 1993) are also present in neurosecretory nerve terminals, as well as in pituicytes, and therefore glutamatergic modulation of hormone secretion has also to be considered.…”
Section: Figurementioning
confidence: 99%